The Pattern of Contextual Meaning of The Quran In Pandemic Context: The New Contextuality Approach In Interpretation - Mahbub Ghozali (Ar-Raniry: International Journal of Islamic Studies, 2022)
This research aims to find a model of the Qur'an's relationship with the COVID-19 pandemic conducted by academics. The relationship of the Qur'an model with the developing context is widely done by referring to contextual methods that some figures have given. However, different aspects are implemented to associate the pandemic with some verses that lexically do not refer to it. This study uses qualitative methods with a type of grounded theory that is strengthened by content analysis as a method of data analysis. The study concluded that the identification of COVID-19 in the Qur'an takes two models: using verses with a scientific understanding and re-narrating theological verses to the impact, treatment, and prevention. The mechanisms performed to associate the Qur'an with COVID-19 in the model are identified in the study by mentioning the methods used through referential analysis and paradigmatic analysis. The referential analysis is used to present new meanings that arise from developing ideas owned by researchers. In comparison, the paradigmatic meaning is used to give new meaning by presenting the COVID-19 narrative in the qur'anic narrative. Judging from the resulting new meaning, the Qur'an's relationship to pandemics is contextual.